2016
DOI: 10.1007/978-94-017-7537-3_10
|View full text |Cite
|
Sign up to set email alerts
|

Integrated, Team-Based Chronic Pain Management: Bridges from Theory and Research to High Quality Patient Care

Abstract: Chronic pain is a significant public health concern. For many, chronic pain is associated with declines in physical functioning and increases in emotional distress. Additionally, the socioeconomic burden associated with costs of care, lost wages and declines in productivity are significant. A large and growing body of research continues to support the biopsychosocial model as the predominant framework for conceptualizing the experience of chronic pain and its multiple negative impacts. The model also informs a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 58 publications
0
12
0
Order By: Relevance
“…Even in patients with full cognitive and physical function, diagnosing chronic pain is difficult. The recommendation is to assess patients with complex chronic pain in specialized pain rehabilitation teams consisting of pain physicians, physiotherapists, psychologists, and if needed, social workers and occupational therapists [ 40 ]. However, according to the clinical experience of the authors, people with IDs seldom have access to such teams and when they do, it is unlikely that team members with specialties other than developmental disorders will have sufficient knowledge and experience to provide care adapted to their special needs.…”
Section: Discussionmentioning
confidence: 99%
“…Even in patients with full cognitive and physical function, diagnosing chronic pain is difficult. The recommendation is to assess patients with complex chronic pain in specialized pain rehabilitation teams consisting of pain physicians, physiotherapists, psychologists, and if needed, social workers and occupational therapists [ 40 ]. However, according to the clinical experience of the authors, people with IDs seldom have access to such teams and when they do, it is unlikely that team members with specialties other than developmental disorders will have sufficient knowledge and experience to provide care adapted to their special needs.…”
Section: Discussionmentioning
confidence: 99%
“…Knowing these risk factors, even if unmodifiable, is important to identify, design and target relevant person-tailored interventions in chronic pain as well as to prevent various adverse outcomes in patients with chronic pain [7]. The findings are also in accordance with the more and more acknowledged biopsychosocial model of (chronic) pain [5]. Biological factors associated with chronic pain include tissue damage and diseases, pain intensity and quality, physical functional interference and sleep disturbance.…”
Section: Pain In the Biopsychosocial Contextmentioning
confidence: 75%
“…It has been argued that a distinction should be made between persons who are affected by pain and who can easily cope on their own, and patients with "pain disease", i. e. with high pain intensity and additional impairment due to elevated degrees of anxiety or depression related to pain, for which treatment in the health care setting is necessary [4]. A prerequisite that persons suffering from chronic pain can deal with their medical condition on their own, is empowerment, giving them skills in patient self-management, and involve them in pain management decision-making together with the health care provider [5]. In fact, another Austrian study in this edition has shown that a higher degree of health literacy in patients with chronic pain is associated with lower pain intensity and lower disability due to pain [6]; therefore, more emphasis on improving health literacy and more courage towards empowering patients with chronic pain towards selfmanagement is necessary.…”
Section: Epidemiological Data and Clinical Needsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, low back pain and migraine enlist among the first five leading causes of years lived with disability (GBD Disease and Injury Incidence and Prevalence Collaborators, 2017). Chronic pain syndromes also cause high direct and indirect costs for the patient, the family and society at large (Park et al, 2015; Driscoll and Kerns, 2016). Prevalence of chronic pain syndromes is substantial, ranging from 2 to 40% of the general population depending on the condition, its epidemiological assessment, and the characteristics of the investigated population by age, gender, and co-morbidity (van Hecke et al, 2013; Henschke et al, 2015).…”
Section: Introductionmentioning
confidence: 99%